Osimertinib as Neoadjuvant Therapy for Resectable Non-Small Cell Lung Cancer: A Case Series - Hu, Yan; Ren, Siying; Yang, Lulu; Tong, Zhongyi; Wang, Ruoyao; Han, Wei; Zeng, Chao; Li, Jina; Xiao, Peng; Wang, Li; Yu, Fenglei; Liu, Wenliang (Frontiers in Pharmacology, 2022)
Background: Evidence of osimertinib as neoadjuvant therapy for resectable non-small cell lung cancer (NSCLC) are currently lacking. This case series study aimed to assess the safety and feasibility of neoadjuvant osimertinib therapy followed by surgery for resectable NSCLC. Materials and methods: Patients with resectable NSCLC with epidermal growth factor receptor (EGFR) mutation who received osimertinib as neoadjuvant therapy followed by surgery at our center were included. Demographic features, radiologic and pathological assessment of response, surgery-related details and complications, toxicity profiles, and prognostic outcomes were extracted. Results: A total of 13 patients were included in this study. The median age at the time of surgical resection was 57 years (interquartile range: 52-64 years), and eight (61.5%) patients were female. The objective response rate (ORR) was 69.2% (9/13), and the complete resection rate was 100%. The rates of pathologic downstaging and lymph node downstaging were 100% (13/13) and 66.7% (6/9), respectively. There were no perioperative deaths and only three (23.1%) patients had postoperative complications. Seven (53.8%) and 13 (100%) patients experienced grade 1 treatment-related adverse reactions and laboratory abnormalities, respectively. No patients experienced drug withdrawal or surgical delays due to the adverse events. No patients showed grade 2 or worse toxicity profiles. One patient was lost to follow-up. The other 12 patients were alive and free of disease recurrence with a median follow-up time of 9.5 months. Conclusion: Neoadjuvant osimertinib therapy seemed to be safe and feasible for resectable EGFR-mutated NSCLC. Future large prospective studies are warranted to confirm whether osimertinib as neoadjuvant therapy outperforms standard tyrosine kinase inhibitors (TKIs) or chemotherapy for resectable EGFR-mutated NSCLC.